Smart Automatic Cooling System with Reduced Humidity Effect for Pet House During Covid-19 Crisis - Afiq Nuruddin Mohd Ainuddin; Nor Azlina Abd Aziz; Wan Zakiah Wan Ismail; Elina Mohd Husini; Khairul Nabilah Zainul Ariffin; Sharma Rao Balakrishnan; Syahida Suhaimi; Irneza Ismail; Juliza Jamaludin (ASM Science Journal, 2024)
Indexed by Scopus/MyCite